2004
DOI: 10.1002/art.20226
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in three ethnic groups. XVIII. Factors predictive of poor compliance with study visits

Abstract: Objective. To determine the baseline factors predictive of poor compliance with study visits in a longitudinal multiethnic lupus cohort study. Methods. Patients with systemic lupus erythematosus (n ‫؍‬ 344) representing a total of 2,069 potential study visits were studied. Of the participants, 24.4% were Hispanic, 43.3% African American, and 32.3% Caucasian. Noncompliance was defined as missing 2 or more study visits. For the purpose of these analyses, visits completed only by review of medical records were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…Lack of adherence to therapy can be as high as 50%, and has been associated with higher persistent disease activity and poorer renal outcomes (70)(71)(72)(73). In addition, the aim of LN treatment is complete renal response but RCT in adult LN have shown that time is needed to reach this response and can be awaited for at least 3-6 months after start of treatment (43).…”
Section: Renal Flares and Refractory Diseasementioning
confidence: 99%
“…Lack of adherence to therapy can be as high as 50%, and has been associated with higher persistent disease activity and poorer renal outcomes (70)(71)(72)(73). In addition, the aim of LN treatment is complete renal response but RCT in adult LN have shown that time is needed to reach this response and can be awaited for at least 3-6 months after start of treatment (43).…”
Section: Renal Flares and Refractory Diseasementioning
confidence: 99%
“…Низкая приверженность терапии у пациентов под-росткового возраста ассоциируется с персистированием более высоких показателей активности и формированием большего ущерба от болезни при сравнительно небольшой продолжительности заболевания [86][87][88]. По данным ли-тературы, комплаенс в этой возрастной группе может соот-ветствовать 50%, при этом тяжесть течения заболевания и частота обострений не гарантируют приверженности ле-чению [89].…”
Section: рекомендация 2 при наличии показаний для изменения схемы леunclassified
“…In contrast to the 'Euro-Lupus' project, the authors of the LUMINA study have split their data into more than 30 partial analyses, describing many diverse aspects such as the early clinical manifestations, 13 the effect of genetic, socio-economic and ethnic factors on disease onset, 14 the influence of poverty and wealth, the predictors of disease activity 15 and of early mortality, 16 or the factors predictive of poor compliance with study visits. 17 The current issue of Lupus publishes three additional original articles from this project, analysing the factors associated with patients being lost to follow-up, 18 the contribution of admixture and socio-economic status to renal involvement, 19 and the factors predictive of a decline to low levels of disease activity. 20 A characteristic of the LUMINA project is the multiethnic nature of its cohort.…”
Section: Editorialmentioning
confidence: 99%